Urgensi Perlindungan Hak Kekayaan Intelektual dalam Era Perdagangan Bebas (Lex Jurnalica, 2015)
Abstract The phenomenon of global economy demands many countries including Indonesia to take part in the global economy. Nonetheless, the global economy has to be followed by globalization of law. Globalization of law takes place by means of standardization of law and international conventions. Participation in WTO-TRIPs has given consequence to the members of state including Indonesia to carry out harmonization in law and regulations, especially, in the field of Intellectual Property Rights. Full compliance and guidline for the members of state of WTO that containing new norms which having higher standard that followed also by the strict law enforcement. The commitment of Indonesia against protection as well as law enforcement in the field of Intellectual Property Rights are being examined. There are many violations such as piracy, counterfeiting and duplication in the works of intellectual property that have made and put to Indonesia in the level of Priority Watch List that considered to be serious and may result retaliation in the field of economy such as decrease of quota, remove of General System of Preferences by the United States of America and other advanced countries. Keywords: Global economy and law, pirate, counterfeiter, harmonization of law, full compliance, Priority Watch List. AbstrakFenomena ekonomi global menuntut negara-negara termasuk Indonesia, untuk berpartisipasi dalam globalisasi ekonomi.Namun, globalisasi ekonomi harus diikuti pula dengan globalisasi hukum.Globalisasi hukum terjadi melalui standarisasi hukum, dan konvensi-konvensi internasional. Keikutsertaan pada WTO-TRIPs, telah member konsekwensi kepada negara-negara anggotanya, termasuk Indonesia, untuk melakukan harmonisasi undang-undang dan peraturannya, terutama dalam bidang Hak Kekayaan Intelektual. Penyesuaian secara penuh atau full compliance serta pedoman bagi negara-negara anggota WTO, yang memuat norma-norma baru, memiliki standar yang lebih tinggi, yang disertai pula oleh penegakan hukum yang ketat. Komitmen Indonesia terhadap perlindungan dan penegakan hukum dalam bidang Hak Kekayaan Intelektual sedang diuji. Banyaknya pelanggaran seperti pembajakan, pemalsuan dan penjiplakan terhadap karya-karya intelektual, telah memasukkan Indonesia kedalam peringkat Priority Watch List, suatu peringkat yang termasuk berat, yang dapat member konsekwensi terjadinya retaliasi dalam bidang ekonomi, seperti pengurangan kuota, hapusnya General System of Preferences oleh Amerika Seritakat serta negara-negara maju lainnya. Kata kunci: Globalisasi ekonomi dan hukum, pembajak, peniruan, Pemalsuan, harmonisasi hukum, full compliance, Priority Watch List